ANDRAGOGICALLY ORIENTED TEACHING METHODS AND VOCATIONAL SCHOOL GRADUATE STUDENTS' TEACHING PRACTICE ACHIEVEMENT - Rismiyanto Rismiyanto; Fitri Budi Suryani (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2022)
Different learner’s educational levels need different teaching method orientations. Adult and young learners are certainly treated by using different teaching method orientation. The independency of college students as adult learners in learning is still oftentimes found in low level. Both college students and lecturers still have big chance to be involved in a learning process which is not yet entirely supported by principles of independent learning.. This condition is quite contradicted with their status as adult learners who should have applied independent learning, and still experienced by the students at English Education Department of Muria Kudus University (EED MKU). The high independency of learning refers to the adult learners that should be involved in Andragogically oriented teaching methods (AOTM), while the low independency of learning refers to the young learners that should be involved in Pedagogically oriented teaching methods (POTM.) This study is aimed at comparing the effectiveness of implementing AOTM and POTM to the students graduating from vocational and non vocational high schools. This is a quantitative study with the population of 87 students joining Speaking for Instructional Purposes (SIP) classes at EED MKU. Teaching practice pre and post tests are used as the instrument of this study. The results indicate that AOTM and POTM give impact to improve the teaching practice achievement of the students both graduating from vocational and non-vocational high schools when comparing the scores of pre-tests and post-tests, but the AOTM and POTM implemented in SIP classes with students graduating from vocational schools and from non-vocational schools do not result in impact on their teaching practice. However, in a certainly different condition the implementation of AOTM and POTM might give more impact to the teaching practice achievement of the students graduating from vocational schools than those graduating from non-vocational schools